If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + K = 243 Reorder the terms: K + T = 243 Solving K + T = 243 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '-1T' to each side of the equation. K + T + -1T = 243 + -1T Combine like terms: T + -1T = 0 K + 0 = 243 + -1T K = 243 + -1T Simplifying K = 243 + -1T
| 2x-10=25 | | 650+30(n-10)= | | 3/4(m-6)=-2 | | 3/4(m-6)=2 | | 1x^2+1+1x^2=5 | | m^2+20m-300=0 | | 1.5y=6 | | n+4N=245 | | k^2-13k+12=0 | | -3p+7=5-(5p+7) | | (3)2X+3Y=75.75 | | (-2)3X+2Y=79.40 | | 174=15x+4X^2 | | -3x-2y-x-5xy+3= | | 6.4+7x(2)=10.9-6x | | 3S+2J=75.78 | | -2x+4=7x-3 | | 6x^2-7-20=0 | | 5x+1=-6x-8 | | -8.2x=65.6 | | 3S+2J=79.40 | | 12(x+3)=3(4x+3)+27 | | -3x-7=x+4 | | -.25(x-8)+.5(x+2)=x+15 | | n^2+7n-60=0 | | 26=4x+16 | | r^2+15r+56= | | 39-15=3(x-2) | | 15+5y=13y-9 | | 4x+18=-5-3x-12 | | x^2+13x=42 | | 25-5x=18+2x |